Analysis of sequence variability in the macronuclear DNA of Paramecium tetraurelia: A somatic view of the germline - Duret, Laurent; Cohen, Jean; Jubin, Claire; Dessen, Philippe; Goût, Jean-François; Mousset, Sylvain; Aury, Jean-Marc; Jaillon, Olivier; Noël, Benjamin; Arnaiz, Olivier; Bétermier, Mireille; Wincker, Patrick; et al.

(untitled) (Genome Research, 2008)
Ciliates are the only unicellular eukaryotes known to separate germinal and somatic functions. Diploid but silent micronuclei transmit the genetic information to the next sexual generation. Polyploid macronuclei express the genetic information from a streamlined version of the genome but are replaced at each sexual generation. The macronuclear genome of Paramecium tetraurelia was recently sequenced by a shotgun approach, providing access to the gene repertoire. The 72-Mb assembly represents a consensus sequence for the somatic DNA, which is produced after sexual events by reproducible rearrangements of the zygotic genome involving elimination of repeated sequences, precise excision of unique-copy internal eliminated sequences (IES), and amplification of the cellular genes to high copy number. We report use of the shotgun sequencing data (>106 reads representing 13× coverage of a completely homozygous clone) to evaluate variability in the somatic DNA produced by these developmental genome rearrangements. Although DNA amplification appears uniform, both of the DNA elimination processes produce sequence heterogeneity. The variability that arises from IES excision allowed identification of hundreds of putative new IESs, compared to 42 that were previously known, and revealed cases of erroneous excision of segments of coding sequences. We demonstrate that IESs in coding regions are under selective pressure to introduce premature termination of translation in case of excision failure.